Pemanfaatan Abu Pembakaran Sekam Batu Bata Sebagai Material Dekorasi Aesthetic Building - Washinton, Rahmad; ranelis; Alipuddin (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Contemporary design today increasingly emphasizes the importance of sustainability and the exploration of local materials as part of visual identity. The use of ash from burned rice-husk brick kilns as a decorative material in architectural design offers an approach that integrates aesthetic value, functionality, and sustainability. This research is motivated by the problem of abundant yet underutilized waste from rice-husk brick combustion, which has the potential to pollute the environment. The ash produced from brick-kiln rice husks possesses distinctive visual characteristics, including natural neutral colors, unique textures, and a rustic impression that can enrich both interior and exterior design expressions.The purpose of this study is to examine the potential of rice-husk ash as a decorative building element that carries aesthetic value while remaining environmentally friendly. The method used involves material experimentation and design based on local context, where the ash is processed into decorative components such as wall ornaments and aesthetic fence elements. The designs emphasize beauty through simplicity. Laboratory tests and field observations were conducted to evaluate color stability, texture, durability, and compatibility with common construction substrates.The results of the study show that the use of rice-husk ash not only enhances the visual character of buildings but also creates a meaningful design narrative rooted in local culture. Thus, ash from rice-husk brick combustion can serve as an innovative solution for creating architectural designs that are aesthetic, contextual, and environmentally friendly, while also expanding the horizons of material exploration in interior and exterior design. In addition, its application can reduce dependence on synthetic decorative materials, thereby lowering environmental impact and supporting sustainable construction practices.